Uncontrolled Hypertension in a Group of Hypertensive Patients in Erbil - Kameran Hassan Ismail; Bushra Baker Khidder (Kufa Journal for Nursing Sciences)
Background: Hypertension is a powerful risk factor for fatal and non-fatal cardiovascular disease events, and many randomized trials showed that hypertension control is associated with a decrease in incidence of stroke and coronary heart disease.